THE EFFECTIVENESS OF GROUP TUTORING SERVICES WITH ART THERAPY TECHNIQUES TO REDUCE NARCISSISTIC BEHAVIOR IN STUDENTS - Sufina Dewi; Saiful Akhyar Lubis (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to determine the effectiveness of group counseling services using art therapy techniques in reducing narcissistic behavior among students. The approach employed is a quantitative method with an experimental research design, specifically a One-Group Pretest-Posttest Design. The research subjects consisted of 21 tenth-grade students (Class X-1) at MAPN 4 Medan who were identified as having high levels of narcissism based on the Narcissistic Personality Inventory (NPI-16) questionnaire. Data analysis techniques included normality test, homogeneity test, and the Wilcoxon Signed Ranks Test. The results of the normality test indicated that the data were not normally distributed (Sig. < 0.05), thus, non-parametric testing was applied. The homogeneity test showed that the variances of pretest and posttest data were homogeneous (Sig. > 0.05). The Wilcoxon test results revealed a significance value of 0.000 (p < 0.05), with all participants scoring lower on the posttest than the pretest, indicating a significant reduction in narcissistic behavior after the intervention. Therefore, group counseling services using art therapy techniques proved to be effective in reducing narcissistic behavior among students.